Analisis Pelaku Kenakalan Remaja “Klitih” dalam Perspektif Teori Asosiasi Diferensial Sutherland - Alma Miftaqiyah; Aryo Anargya Hakim Putra; Chieka Aisyah Kinanti; Dela Novi Ardani; Nadya Petricia Lubis; Sylmi Adila (Universitas Katolik Widya Karya Malang, 2023)
This study aims to analyze the forms of deviant behavior commonly practiced by teenagers, one of which is